Racism and Aboriginal child health: An exploration using the LSIC - Priest, Naomi C.; Cooper, Matthew N.; Farrant, Brad M.; Shepherd, Carrington C.J.; Li, Jianghong; Hopkins, Katrina D. (My University, 2016)
Background: Few Australian studies have examined the relationship between racism and Aboriginal child health. We aim to provide contemporary insights on the relative importance of racism as a determinant of Aboriginal child health and health inequalities. Methods: We examined the relationship between racism and a range of physical and mental health indicators for Aboriginal children aged 5-10 years, and included a focus on population attributable risks (PARs). We analysed the Longitudinal Study of Indigenous Children using multivariate logistic regression within a multilevel framework. Results: There was generally a significant positive-association between measures of racism and physical and mental health—this applied to mental health status, sleep difficulties, obesity and asthma, but not general health and injury. Effect sizes tended to be larger for those exposed to persistent racism, and are suggestive of a dose-response relationship between racism and health. Children’s direct experiences of racism accounted for 15.9% (95% CI: 10.8-20.9%) of the PAR for mental health status, 18.4% (95% CI: 13.1-23.7%) of the PAR for sleep difficulties and 13.6% (95% CI: 6.1-21.1%) of the PAR for asthma, while family experiences of racism accounted for 11.8% of the PAR for obesity (95% CI: 0.2-23.5%). Conclusions: The results are consistent with the limited extant literature and further confirms that racism is a critical determinant of the health of Aboriginal children. The findings support the notion that eliminating racism is likely to reduce the burden associated with some important health problems in childhood and therefore reduce health disparities between Aboriginal and non-Aboriginal children.
Keywords: Disadvantage, adversity and resilience; Culture and language; Health and wellbeing; Culture, identity and language; Adversity and resilience; Dsiadvantage, adversity and resilience; Health and wellbeing; Culture and identity